Penile Squamous Cell Carcinoma: Penis-Preserving Treatment With Mohs Micrographic Surgery. Issue 8 (August 2016) - Machan, Mac; Brodland, David; Zitelli, John
Abstract : BACKGROUND: There have been few published case series of penile squamous cell carcinoma (SCC) removed with Mohs micrographic surgery (MMS). Of these case series, the published cure rates are between 68% and 74%. OBJECTIVE: To report 30 years of experience removing penile SCCs with MMS. METHODS and Materials: Retrospective record review of 42 patients with 44 penile SCCs. RESULTS: There was one recurrence of the 19 primary SCCs in situ, resulting in a cure rate of 94.7%. There were no recurrences among the 10 primary invasive SCC. Of the 6 recurrent invasive SCCs, 2 recurred, resulting in an initial cure rate of 66.7%. These 2 recurrences were re-treated with MMS with no evidence of recurrence at 5 years. There were 4 patients with SCC in situ of the glans with extension down the urethra. While all 4 patients required urethral dilation postoperatively secondary to urethral stricture, none of these tumors recurred and normal function was restored in each case. CONCLUSION: In conclusion, MMS may be preferred for patients with penile carcinoma by providing a high cure rate and tissue conservative alternative to partial or total penectomy and does not need to be limited to low-grade, small, superficial tumors.